Examining What Variables Lead to Improved Outcomes for Club Sports Participants. Issue 2 (October 2019) - Lifschutz, Leon
Student affairs and campus recreation practitioners trumpet the values of cocurricular experiences and believe that they can have a deep impact on key learning outcomes for participants. This study surveys club sports participants at the University of Vermont to assess club sports participant satisfaction, belonging, and participations impact on key outcomes. The study affirms the reliability and validity of the survey instrument through strong internal consistency scores and factor analysis. It also positively affirms a positive relationship between key variables such as satisfaction and belonging to key outcomes. A final key finding of this study is the statistically significant effect of belonging scores on key outcomes.